(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
The sustainable development of a national economy increasingly depends on the effective integration of foreign investment and entrepreneurial activity. Foreign Direct Investment (FDI) serves as a major source of capital inflow, technological diffusion, and global market integration, while entrepreneurship stimulates innovation, job creation, and economic diversification. According to recent global reports, FDI inflows reached approximately 1.3 trillion worldwide in 2023, demonstrating its continued importance despite global economic uncertainty. At the same time, small and medium-sized enterprises (SMEs), driven by entrepreneurial initiatives, account for over 90% of businesses and more than 50% of employment globally. This paper provides a comprehensive analysis of how these two forces interact and contribute to national economic growth, particularly in developing economies. It also examines structural challenges and offers policy recommendations for maximizing their impact.